Spectrum of chemical analysis of 150 consecutive upper urinary tract stones with critical analysis in respect of demographic and geographical distribution - Islam, Waliul; Naser, Fazal; Hasan, Mahmood; Rahman, Mohammed Mizanur; Rahman, Mizanur; Hossain, Shohrab (International Surgery Journal, 2021)
Background: The aim of the study was to evaluate the chemical composition of urinary stones and pattern of changes according to the patient's demographic and geographical distribution. Methods: 150 patients of upper tract urolithiasis were prospectively selected during the study period. Chemical composition was analyzed by FTIR spectroscopy. A subgroup study based on the patient's age, sex and geographical origin was done. For subgroup analysis patients were divided into two age groups; group A (5-18 years, 14 patients) and group B (>18 years, 136 patients). The geographical origin of the patients was recorded according to the administrative division. Results: Male were predominant in all age groups with ratio of 2.49:1. Most of the patients were from Rangpur (28.67%) and Mymensingh (20.67) division. Mixed composition stones were much more common than pure one (75.99% vs 24.01%). Overall, combination of calcium oxalate monohydrate with dehydrate was the most common composition (56.67%). Calcium oxalate was the predominant chemical composition in 82% of stones, followed by struvite in 9.33%, apatite in 4.67%, uric acid in 3.33% and cystine in 0.67%. The proportion of calcium oxalate stone was increasing while that of struvite, uric acid, and cystine stone was decreasing with age. But stone composition did not show any significant difference on geographical distribution. Conclusions: Calcium oxalate is the most common composition of urinary stones in all age groups. Mixed stones are more common than pure ones. The incidence of calcium oxalate stone increases while that of struvite, uric acid, and cystine stone decreases with age.